PENGARUH PROMOSI PENJUALAN DAN ATMOSFER TOKO TERHADAP PEMBELIAN IMPULSIF DENGAN EMOSI POSITIF SEBAGAI VARIABEL INTERVENING PADA KONSUMEN SUPERINDO TLOGOMAS MALANG - Rizal Ahmad Alfarizi; N Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
AbstractThis research aims to analyze the impact of Sales Promotion and Store Atmosphere towards Impulse Buying through consideration of Positive Emotion at Superindo Tlogomas Malang. This research will be conducted by distributing questionnaires to 99 respondents which are consumer of Superindo. Quantitative analysis with path analysis analysis model method were used for the technical analysis.The results of this study indicate that the sales promotion influence positively and significantly related to impulse buying, store atmosphere affect positively and significantly related to impulse buying, positive emotion in a positive and significant impact on impulse buying.Keywords: Sales Promotion, Store Atmosphere, Impulse Buying.